Missed Opportunities for Preventing Perinatal Transmission of Human Immunodeficiency Virus, Florida, 2007–2014. Issue 2 (February 2017) - Trepka, Mary Jo; Mukherjee, Soumyadeep; Beck-Sagué, Consuelo; Maddox, Lorene M.; Fennie, Kristopher P.; Sheehan, Diana M.; Prabhakar, Maithri; Thompson, Dan; Lieb, Spencer
Abstract : Objectives: Despite declining numbers of perinatally exposed infants, an increase in perinatal human immunodeficiency virus (HIV) infections from 2011 to 2013 prompted this study to identify missed perinatal HIV prevention opportunities. Methods: Deidentified records of children born from 2007 through 2014, exposed to HIV perinatally, and reported to the Florida Department of Health were obtained. Crude relative risks (RRs) and 95% confidence intervals (CIs) for factors associated with perinatal transmission, nondiagnosis of maternal HIV infection, and nonreceipt of antiretroviral medication were calculated. Results: Of the 4337 known singleton births exposed to maternal HIV infection, 70 (1.6%) were perinatally infected. Among perinatal transmission cases, more than one-third of mothers used illegal drugs or acquired a sexually transmitted infection during pregnancy. Perinatal transmission was most strongly associated with maternal HIV diagnosis during labor and delivery (RR 5.66, 95% CI 2.31–13.91) or after birth (RR 26.50, 95% CI 15.44–45.49) compared with antenatally or prenatally. Among the 29 women whose infection was not known before pregnancy and whose child was perinatally infected, 18 were not diagnosed during pregnancy; 12 had evidence of an acute HIV infection, and 6 had no prenatal care. Conclusions: Late diagnosis of maternal HIV infection appeared to be primarily the result of acute maternal infections and inadequate prenatal care. In Florida, effective programs to improve utilization of prenatal care and detection and primary prevention of prenatal acute infection are needed. Abstract : This article examines the missed opportunities to prevent perinatal human immunodeficiency virus (HIV) transmission in the state of Florida. Deidentified data for the years 2007–2014 obtained from the Florida Department of Health were used. Seventy (1.6%) cases of perinatal transmission were observed among the 4337 known singleton births to mothers who were infected with HIV. Diagnosis of maternal HIV infection during labor and delivery or after birth was associated with a higher risk for perinatal transmission. Having an acute HIV infection and not having antenatal care were common among cases of perinatal transmission.